2018
DOI: 10.2174/1573409914666180321111925
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Dynamic Simulation Studies of Terpenoids of I. wightii (Bentham) H. Hara against Acetylcholinesterase and Histone Deacetylase3 Receptors

Abstract: In silico and in vitro studies suggest that abietic acid could be a promising terpenoid for treating Alzheimer's disease and cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The selection of docking results in this study was based on results that showed complete protein binding and density. X-Ray (RMSD) detected a value of 2 Å (Ramnath et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of docking results in this study was based on results that showed complete protein binding and density. X-Ray (RMSD) detected a value of 2 Å (Ramnath et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…AA has strong binding efficiency with the AchE and HDAC3 receptors, as indicated by Ligplot analysis and root mean square deviation analysis. In vitro tests with HeLa cells showed that abietic acid induces apoptosis in a concentration-dependent manner, suggesting its potential as a promising terpenoid for treating Alzheimer’s disease and cervical cancer ( Ramnath et al, 2018 ).…”
Section: Anticancer Activities Of Aamentioning
confidence: 99%
“…Roy et al explored the effect of curcumin on SiHa cells and reported that both HDAC1/2 and HPV inhibition resulted in cell cycle arrest at the G1/S phase by alteration of cell cycle regulatory proteins [ 127 ], while Ramnath et al revealed that the terpenoid abietic acid was docked with HDAC3 receptors in HeLa cells, hence inducing apoptosis in a concentration-dependent manner [ 128 ].…”
Section: Phytopharmaceuticalsmentioning
confidence: 99%